2021
DOI: 10.3390/pharmaceutics13081312
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured Lipid Carriers (NLCs) for Oral Peptide Drug Delivery: About the Impact of Surface Decoration

Abstract: This study was aimed to evaluate the impact of surfactants used for nanostructured lipid carriers (NLCs) to provide enzymatic protection for incorporated peptides. Insulin as a model peptide was ion paired with sodium dodecyl sulfate to improve its lipophilicity. Three NLC formulations containing polyethylene glycol ester (PEG-ester), polyethylene glycol ether (PEG-ether), and polyglycerol ester (PG-ester) surfactants were prepared by solvent diffusion method. NLCs were characterized regarding particle size, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 41 publications
(55 reference statements)
0
7
0
Order By: Relevance
“…It was found that increasing the degree of glycerol esterification resulted in a significant increase in ZP value. This is attributed to the negative charge produced by the free carboxylic group in the free FA [ 26 ]. The present results are in agreement with various studies that showed that NLC prepared from LCFA has a ZP value less than LCM and LCT [ 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…It was found that increasing the degree of glycerol esterification resulted in a significant increase in ZP value. This is attributed to the negative charge produced by the free carboxylic group in the free FA [ 26 ]. The present results are in agreement with various studies that showed that NLC prepared from LCFA has a ZP value less than LCM and LCT [ 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…The addition of spatially incompatible liquid lipid(s) to the formulations is beneficial in two aspects, it leads to the formation of a less-ordered crystalline structure ( Figure 2 ), ensuring extra area for drug loading, decreases the crystalline degree of the lipid matrix and averts drug expulsion [ 128 , 167 ]. Usually, the liquid lipid is included up to 30% of the total lipid amount in the NLCs formulations [ 168 , 169 ]. As such, researchers often use castor/olive/argan oil, oleic acid, Miglyol ® 812 (medium-chain triglycerides), propylene glycol dicaprylocaprate—Labrafac™ PG (Gattefosse, Saint-Priest, France), or caprylocaproyl macrogol-8 glycerides—Labrasol ® (Gattefosse, Saint-Priest, France) [ 170 , 171 , 172 ].…”
Section: Feasibility Of Lipid Nanoparticles In Ophthalmologymentioning
confidence: 99%
“…Chitosan also opens intercellular spaces of enterocytes and facilitates drug penetration. The P-glycoprotein (Pgp) inhibition reduced the drug efflux, while enhancing their adsorption and penetration [ 59 , 60 ]. Phospholipid-containing liposomes (liquid) are disrupted upon exposure to 10 mM bile salts, losing the entire payload [ 61 ].…”
Section: Lipid-based Nanocarriers For Oral Drug/vaccine Deliverymentioning
confidence: 99%